2009
DOI: 10.1111/j.1600-0854.2009.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome Function: Sometimes Less Is More

Abstract: Tight regulation of centrosome duplication is critical to ensure that centrosome number doubles once and only once per cell cycle. Superimposed onto this centrosome duplication cycle is a functional centrosome cycle in which they alternate between phases of quiescence and robust microtubule (MT) nucleation and MT‐anchoring activities. In vertebrate cycling cells, interphase centrioles accumulate less pericentriolar material (PCM), reducing their MT nucleation capacity. In mitosis, centrosomes mature, accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 83 publications
(120 reference statements)
2
29
0
Order By: Relevance
“…While most microtubules are nucleated by g-TuRCs (Teixidó-Travesa et al, 2012), nucleation has also been found to be facilitated by several microtubule plus end-binding proteins (Rogers et al, 2008;Rusan and Rogers, 2009) S7). The noncanonical microtubule initiations we describe in this article are most likely not derived from g-TuRC complexes because of the absence of GCP2-3xGPF marker at the cell cortex during the disassembly phase, suggesting that another factor may serve as the nucleator or that initiations may arise from stabilized short fragments of microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…While most microtubules are nucleated by g-TuRCs (Teixidó-Travesa et al, 2012), nucleation has also been found to be facilitated by several microtubule plus end-binding proteins (Rogers et al, 2008;Rusan and Rogers, 2009) S7). The noncanonical microtubule initiations we describe in this article are most likely not derived from g-TuRC complexes because of the absence of GCP2-3xGPF marker at the cell cortex during the disassembly phase, suggesting that another factor may serve as the nucleator or that initiations may arise from stabilized short fragments of microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of Cep57 could therefore cause spindle microtubule disorganization and PCM instability, which would cause some PCMs to be pulled out by microtubule-mediated forces. Those PCM fragments do not contain centrioles but are able to recruit other PCM components and nucleate microtubules [35], eventually forming new spindle poles.…”
Section: Discussionmentioning
confidence: 99%
“…The PCM includes hundreds of proteins, including many large scaffold proteins that function as regulatory-protein docking sites (Doxsey et al, 2005), and the ctubulin ring complexes that are responsible for microtubule nucleation (Doxsey et al, 2005;Kreitzer et al, 1999). The centrosome and the microtubule system are intimately connected, and deficiencies in either microtubule or centrosome function can reduce cell survival (Mazzorana et al, 2011;Rusan and Rogers, 2009). Moreover, because the centrosome and microtubules reciprocally influence the function of each other, we studied the impact of TIG3 on both the centrosome and the microtubules.…”
Section: Discussionmentioning
confidence: 99%